A simple method to improve the antibiotic elution profiles from polymethylmethacrylate bone cement spacers by using rapid absorbable sutures - Tzu-Hao Tseng; Chih-Hao Chang; Chien-Lin Chen; Hongsen Chiang; Hao-Ying Hsieh; Jyh-Horng Wang; Tai-Horng Young (BMC Musculoskeletal Disorders, 2022)
Abstract Objective Antibiotic-loaded bone cement beads and spacers have been widely used for orthopaedic infection. Poor antibiotic elution is not capable of eradicating microbial pathogens and could lead to treatment failure. The elution profiles differ among different cement formulations. Although Simplex P cement has the least release amount, it is widely used due to its ready availability. Previous methods aiming to improve the elution profiles were not translated well to clinical practice. We sought to address this by using easily available materials to improve the elution profile of antibiotics from PMMA, which allows clinicians to implement the method intraoperatively. Methods Vancomycin was mixed with Simplex P cement. We used Vicryl Rapide sutures to fabricate sustained-release cement beads by repetitively passing the sutures through the beads and/or mixing suture segments into the cement formulation. Vancomycin elution was measured for 49 days. The mechanism of antibiotic release was observed with gross appearance and scanning electron microscopic images. The antimicrobial activities against MRSA were tested using an agar disk diffusion bioassay. Results Passing Vicryl Rapide sutures through cement beads significantly improved the elution profiles in the 7-week period. The increased ratios were 9.0% on the first day and 118.0% from the 2nd day to the 49th day. Addition of suture segments did not increase release amount. The Vicryl Rapide sutures completely degraded at the periphery and partially degraded at the center. The antibiotic particles were released around the suture, while antibiotic particles kept densely entrapped in the control group. The antimicrobial activities were stronger in passing suture groups. Conclusion Passing fast absorbable sutures through PMMA cement is a feasible method to fabricate sustained-release antibiotic bone cement. Intra-cement tunnels can be formed, and the effect can last for at least 7 weeks. It is suitable for a temporary spacer between two stages of a revision surgery.